(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
This study reports on the effect of magnesium oxide, magnesium trisilicate, aluminium hydroxide and bentonite antacids on the disintegration and dissolution characteristics of commercial paracetamol and metronidazole tablets. The effect of salt on the interaction between the drugs and the antacids was also studied. The disintegration times of the tablets were determined in the different antacid solutions while the effect of antacids on dissolution was studied by adding various amounts of the antacid powders to the dissolution medium. The presence of magnesium trisilicate, magnesium oxide and bentonite delayed disintegration of paracetamol tablets. Generally, the introduction of 7.5% w/w sodium chloride into each of the antacid resulted in a reduction in disintegration time of paracetamol tablets. Combination of the antacids resulted in a greater retardation of dissolution of the paracetamol and metronidazole tablets. The retardation of dissolution of metronidazole from the tablets followed the rank order: bentonite > magnesium trisilicate > magnesium oxide > aluminium hydroxide. The addition of salt to magnesium trisilicate and bentonite dissolution medium decreased T50 and T70 with 7.5% w/w sodium chloride causing a greater reduction than 5.0% w/w. The results suggest that concomitant administration of magnesium oxide, magnessium trisilicate, aluminium hydroxide and bentonite with paracetamol and metronidazole should be discouraged since the bioavailability of these drugs may be compromised.